2022
DOI: 10.1177/00104140221089653
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of Rural Underdevelopment: Evidence from Land Reform in Italy

Abstract: Patchiness in rural development remains a salient feature of many developed and developing countries that have struggled historically to overcome enormous national disparities in economic structure and well-being. This paper examines how one major, explicit rural policy ostensibly aimed at rural advancement—land reform—can impact uneven development in the countryside. It does so in Italy, where a major land reform redistributed large landholdings to individual peasant families after World War II. Based on orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…What are the long-term consequences of these patterns for Polish democracy and dissent? Albertus and Schouela (2022) find that social mobilization under a dictatorship increases support for democracy in the long run. The missing resistance in some areas with surviving traditional elites in Poland could thus imply that these places had missed an important process that would consolidate democratic support in the long run.…”
Section: Discussionmentioning
confidence: 87%
“…What are the long-term consequences of these patterns for Polish democracy and dissent? Albertus and Schouela (2022) find that social mobilization under a dictatorship increases support for democracy in the long run. The missing resistance in some areas with surviving traditional elites in Poland could thus imply that these places had missed an important process that would consolidate democratic support in the long run.…”
Section: Discussionmentioning
confidence: 87%
“…Research on the long-term effects of war experiences -and on historical legacies more generally -has begun to account for factors that mediate long-term effects. Recent studies have identified conditions under which the past can affect the present, including the degree to which present events resemble the past (Fouka and Voth 2023), the presence of clandestine networks (Villamil 2020), the absence of credible threats of retribution (Rozenas and Zhukov 2019), local communities' capacity to bypass revisionist efforts (Villamil 2022), regime's efforts to co-opt social mobilization (Albertus and Schouela 2024) and the degree to which collective memory is institutionalized (Fouka and Voth 2023). Furthermore, legacies have been found to be transmitted through family socialization (Nunn and Wantchekon 2011;Voigtländer and Voth 2012;Lupu and Peisakhin 2017), community composition (Charnysh and Peisakhin 2022), peer and neighbor effects (Cho, Gimpel, and Dyck 2006), and educational and religious institutions (Wittenberg 2006).…”
Section: Wartime Political Legaciesmentioning
confidence: 99%
“… Ruggeri (2015a, 2018),Osorio, Schubiger, and Weintraub (2021),Rizkallah (2016),Fontana, Nannicini, and Tabellini (2023),Arias and Calle (2021),. andAlbertus and Schouela (2024).4. Exceptions includeOsorio, Schubiger, and Weintraub (2021),Lazarev (2019),Arias and Calle (2021),Fouka and Voth (2023),Costalli et al (2024), andWayne, Damann, andFachter (2023).…”
mentioning
confidence: 99%